Formal Modelling of an Autonomic Service Oriented Architecture - Bhakti , M. A. C. (2011)
Service oriented architecture (SOA) is improving conventional software architecture by enabling composition of large and complex system out of simpler software services. However, implementation of SOA brings about some challenges, including its adaptability and robustness. A more robust service architecture that is capable of changing its structure and functionality autonomously, i.e. with little human intervention, is required due to the increased complexity and dynamism of the current network systems. In this paper, we propose the adaptation of autonomic computing paradigm into SOA to improve its robustness, and we also elaborate the formal modelling of the proposed autonomic SOA.